Cured body of hydraulic composition
A cured product with alkali-resistant fibers and controlled pore volumes addresses the need for high impact resistance, dimensional stability, and low water absorption, enhancing bending strength for building materials.
Patent Information
- Application Number
- JP2024185872
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-04-28
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-27
AI Technical Summary
Existing cured products lack high impact resistance, dimensional stability, and bending strength while maintaining low water absorption.
A cured product of a hydraulic composition containing alkali-resistant fibers, calcium silicate, and calcium aluminate, with specific pore volume ratios and limited calcium oxide, calcium hydroxide, and calcium carbonate crystals, is developed to enhance strength and stability.
The composition achieves high impact resistance, dimensional stability, and low water absorption with improved bending strength, suitable for building material boards.
Smart Images

Figure 2024180795000001
Abstract
Description
[Technical field]
[0001] This patent application claims priority under the Paris Convention based on Japanese Patent Application No. 2023-74534 (filed April 28, 2023), the entire contents of which are incorporated herein by reference. The present invention relates to a hardened product of a hydraulic composition and a building board comprising the hardened product. [Background technology]
[0002] Although hydraulic compositions containing cement are highly versatile materials, the cement manufacturing process generates large amounts of carbon dioxide. Therefore, in order to reduce the impact on climate change, there are efforts to reduce the amount of cement used in the civil engineering and construction sectors.
[0003] For example, Patent Document 1 describes a cement-free hardening composition that uses ground granulated blast furnace slag, hydrated lime, and, if necessary, fly ash or silica fume as a binder that does not use any cement at all, and that is characterized by mixing this binder with a high-performance air-entraining water-reducing agent such as a polycarboxylic acid-based agent, if necessary, a water-soluble admixture whose main components are multiple inorganic compounds such as calcium ions, magnesium ions, sodium ions, and alkali metal ions, and fresh water. Patent Document 2 describes an inorganic board that is a hardened mat formed by dehydrating a slurry containing blast furnace slag, gypsum, an alkaline material, reinforcing fibers, and inorganic admixtures, and that is suitable for use as a building board while keeping the cement content to 0 to 11 mass %. Furthermore, Patent Document 3 describes a laminated molded plate comprising two or more molded plates formed from a hardenable composition containing a specific amount of a specific blast furnace slag as an aluminosilicate source, an alkaline metal hydroxide, cellulose-based fibers, and alkali-resistant fibers. Furthermore, Patent Document 4 describes a hardened body of a hardenable composition containing a specific amount of blast furnace slag as an aluminosilicate source, an alkali activator, and an alkali-resistant fiber, the hardened body having a specific moisture content. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication 2012-171855 [Patent Document 2] Patent Publication No. 2013-216534 [Patent Document 3] International Publication No. 2022 / 004640 [Patent Document 4] International Publication No. 2022 / 004643 Summary of the Invention [Problem to be solved by the invention]
[0005] However, there is still a demand for cured products having higher bending strength and impact resistance while maintaining dimensional stability and low water absorption. Therefore, an object of the present invention is to provide a hardened product of a hydraulic composition having high impact resistance, high dimensional stability, low water absorption, and high bending strength. [Means for solving the problem]
[0006] The present inventors have conducted extensive research to solve the above problems and have completed the present invention. That is, the present invention includes the following preferred embodiments. [1] A hardened body of a hydraulic composition, The hardened body includes an alkali-resistant fiber, a calcium silicate, and a calcium aluminate, A hardened body, in which the ratio of the volume of pores in the range of 11 to 300,000 nm to the volume of pores in the range of 6 to 10 nm in a pore size distribution of the hardened body determined by mercury intrusion porosimetry is 14 or less. [2] The hardened body according to [1], wherein the total content of calcium oxide, calcium hydroxide and calcium carbonate crystals as measured by powder X-ray diffraction is 15 mass% or less based on the mass of the hardened body excluding the fiber component. [3] The cured product according to [1] or [2], wherein the average fiber diameter of the alkali-resistant fibers is 3 to 900 μm. [4] The cured product according to any one of [1] to [3], wherein the aspect ratio of the alkali-resistant fiber is 30 to 2,500. [5] The cured product according to any one of [1] to [4], wherein the alkali-resistant fiber has a tensile strength of 5 cN / dtex or more. [6] The cured product according to any one of [1] to [5], wherein the alkali-resistant fiber is one or more types of fiber selected from the group consisting of polyvinyl alcohol-based fibers, polypropylene fibers, and polyethylene fibers. [7] The hardened body according to any one of [1] to [6], wherein the hydraulic composition contains, based on the total solid content of the hydraulic composition, 8 to 72 mass% of cement, 72 to 18 mass% of slag, 0.5 to 12 mass% of slaked lime, and 0.1 to 5 mass% of alkali-resistant fiber. [8] The hardened body according to [7], wherein the average particle size of the slaked lime is 3 to 600 μm. [9] The hardened body according to any one of [1] to [8], further comprising 0.1 to 10 mass % of pulp based on the mass of the hardened body.
[10] The hardened body according to any one of [1] to [8], wherein the hardened body does not contain pulp and has a water absorption of 1 to 25% as determined in accordance with JIS A 5430:2018.
[11] The hardened body according to [9], wherein the water absorption of the hardened body measured in accordance with JIS A 5430:2018 is 5 to 40%.
[12] The hardened body according to any one of [1] to
[11] , wherein the pore volume in the range of 6 to 10 nm in the pore size distribution of the hardened body measured by mercury intrusion porosimetry is 0.05 mL / g or more.
[13] The cured body according to any one of [1] to
[12] , wherein the pore volume in the range of 11 to 300,000 nm in the pore size distribution of the cured body measured by mercury intrusion porosimetry is 0.3 to 3.0 mL / g.
[14] A building board comprising the cured product according to any one of [1] to
[13] . Effect of the Invention
[0007] According to the present invention, it is possible to provide a hardened product of a hydraulic composition having high impact resistance, high dimensional stability, low water absorption, and high bending strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, the embodiments of the present invention will be described in detail. Note that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention.
[0009] [Cured body] The hardened body of the present invention is a hardened body of a hydraulic composition, the hardened body containing an alkali-resistant fiber, calcium silicate and calcium aluminate, and the ratio (B) / (A) of the pore volume (B) in the range of 11 to 300,000 nm to the pore volume (A) in the range of 6 to 10 nm in the pore size distribution of the hardened body measured by mercury intrusion porosimetry is 14 or less.
[0010] The reason why the hardened body of the present invention has high impact resistance, high dimensional stability, low water absorption, and high bending strength is not clear, but the following mechanism of action is presumed. The hardened body of the present invention can be produced, for example, by hardening a hydraulic composition comprising cement, slag, slaked lime, and alkali-resistant fibers. In the hardening process, not only the hydration reaction of cement occurs, but also the silicon and aluminum contained in the slag react with the slaked lime. Unlike ordinary geopolymer-like hardening reactions, the reaction proceeds mainly on the surface of the slag, so the amount of calcium required is not so large. In addition, the reaction is relatively slow, and fine and dense pores are formed. Water is unlikely to penetrate into the fine pores. In addition, the fine pores are unlikely to inhibit the adhesion between the fibers and the matrix, so the reinforcing effect of the fibers is unlikely to decrease, and as a result, the hardened body can exhibit high strength and impact resistance. Furthermore, since the reaction proceeds on the slag surface without requiring a large amount of calcium, the amount of cement and slaked lime used can be reduced, and relatively large pores are unlikely to be formed. As a result, it is presumed that the cured product of the present invention has high impact resistance, high dimensional stability, low water absorption, and high bending strength, although the above is merely presumed and the present invention is not limited to this mechanism of action.
[0011] Calcium silicate and calcium aluminate are produced as the hardening of a hydraulic composition containing cement and slag progresses, and are usually contained in the hardened body as hydrates, i.e., calcium silicate hydrate (calcium silicate hydrate) and calcium aluminate hydrate (calcium aluminate hydrate), respectively.
[0012] The total content of calcium silicate and calcium aluminate contained as crystals in the hardened body is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, based on the mass of the hardened body excluding the fiber component, and the upper limit is not particularly limited, but may be 50% by mass or less, 40% by mass or less, 30% by mass or less, or 10% by mass or less. The total content is preferably 1 to 50% by mass, more preferably 2 to 40% by mass, and even more preferably 3 to 10% by mass, based on the mass of the hardened body excluding the fiber component. When the total content is equal to or more than the lower limit and equal to or less than the upper limit, or within the range, the hardened body can have a higher bending strength. The total content can be adjusted to be equal to or more than the lower limit and equal to or less than the upper limit, or within the range, for example, by adjusting the amount of the pozzolanic reactive material and calcium source, such as cement, slag, and slaked lime, in the hydraulic composition. The total content, the respective contents of calcium oxide, calcium hydroxide and calcium carbonate contained as crystals in the hardened body described later, and the total content of calcium oxide, calcium hydroxide and calcium carbonate contained as crystals in the hardened body described later can be measured using powder X-ray diffraction, for example, by the method described in the Examples described later.
[0013] The alkali-resistant fiber has the effect of increasing the impact resistance and bending strength of the hardened body, and further has the effect of preventing a decrease in the impact resistance and / or bending strength of the hardened body by suppressing cracks that may occur during the curing and drying process of the hydraulic composition.
[0014] The alkali-resistant fiber may be inorganic or organic as long as it has chemical durability against alkali. Examples of alkali-resistant inorganic fibers include alkali-resistant glass fibers, steel fibers, stainless steel fibers, and carbon fibers. Examples of alkali-resistant organic fibers include various alkali-resistant fibers such as polyvinyl alcohol (hereinafter sometimes referred to as "PVA")-based fibers, polyolefin-based fibers (e.g., polyethylene fibers and polypropylene fibers), ultra-high molecular weight polyethylene fibers, polyamide-based fibers (e.g., polyamide 6, polyamide 6,6, and polyamide 6,10), aramid fibers (especially para-aramid fibers), polyparaphenylene benzobisoxazole-based fibers (e.g., polyparaphenylene benzoxazole (PBO) fibers), nylon fibers, acrylic fibers, rayon-based fibers (e.g., polynosic fibers and solvent-spun cellulose fibers), acetate-based fibers, polyphenylene sulfide fibers (PPS fibers), and polyether ether ketone fibers (PEEK fibers). These alkali-resistant fibers may be used alone or in combination of two or more. In this specification, different types of alkali-resistant fibers include not only different types of fiber-constituting systems, such as polyvinyl alcohol-based fibers and polyolefin-based fibers, but also different physical properties of fiber-constituting materials, such as polyvinyl alcohol-based fibers with different degrees of polymerization and / or saponification.
[0015] Among these fibers, polyvinyl alcohol-based fibers, polypropylene fibers, and polyethylene fibers are preferably used because they can impart superior reinforcing properties to the cured body and can be produced at low cost. Therefore, in one embodiment of the present invention, the alkali-resistant fiber is preferably one or more fibers selected from the group consisting of polyvinyl alcohol-based fibers, polypropylene fibers, and polyethylene fibers.
[0016] In a preferred embodiment of the present invention, the alkali-resistant fiber is preferably a polyvinyl alcohol fiber. When the alkali-resistant fiber is a polyvinyl alcohol fiber, a cured body having higher impact resistance or higher bending strength, especially high bending strength, can be obtained. The reason is not clear, and it is not intended to be limited to the following reason, but the polyvinyl alcohol fiber produced by solution spinning is easily fibrillated because the molecular structure of the resin in the fiber is less entangled, and when the cured body is destroyed, it is considered that the polyvinyl alcohol fiber fibrillates in the process, absorbing the destruction energy, and bringing impact resistance or bending strength, especially bending strength, to the cured body.
[0017] The average fiber diameter of the alkali-resistant fiber is preferably 3 to 900 μm, more preferably 4 to 300 μm, even more preferably 5 to 50 μm, even more preferably 5 to 30 μm, and most preferably 8 to 25 μm. In addition, the preferred average fiber diameter for each construction method is 5 to 15 μm in a system that does not use aggregate, and 15 to 40 μm in a system that uses aggregate. When the average fiber diameter of the alkali-resistant fiber is within the above range, such an alkali-resistant fiber has sufficient fiber strength and can be industrially stably produced, and the fibers can be more uniformly dispersed in the hydraulic composition or hardened body. The average fiber diameter of the alkali-resistant fiber can be obtained by randomly taking 100 fibers, measuring the fiber diameter at the center of each fiber in the length direction with an optical microscope, and calculating the average value.
[0018] The average fiber length of the alkali-resistant fiber is preferably 1 to 40 mm, more preferably 1.5 to 18 mm, and even more preferably 2 to 10 mm, from the viewpoint of achieving both good dispersibility of the fiber in the hydraulic composition and good reinforcing properties of the hydraulic composition after hardening. The average fiber length of the alkali-resistant fiber and the tensile strength described later can be determined in accordance with JIS L 1015:2010.
[0019] From the viewpoint of achieving both good dispersibility of the fibers in the hydraulic composition and good reinforcing properties after the hydraulic composition is hardened, the aspect ratio of the alkali-resistant fiber is preferably 30 to 2500, more preferably 50 to 1000, and further preferably 200 to 600. The aspect ratio means the ratio of the fiber length to the fiber diameter (fiber length / fiber diameter). The aspect ratio of the alkali-resistant fiber can be calculated from the average fiber length and average fiber diameter described above.
[0020] The tensile strength of the alkali-resistant fiber is preferably 5 cN / dtex or more, more preferably 8 cN / dtex or more, even more preferably 10 cN / dtex or more, and even more preferably 13 cN / dtex or more. When the tensile strength of the alkali-resistant fiber is equal to or more than the lower limit, the reinforcing performance of the cured body can be increased. The upper limit of the tensile strength of the alkali-resistant fiber is appropriately set according to the type of fiber, and may be, for example, 30 cN / dtex or less, 25 cN / dtex or less, or 20 cN / dtex or less. The tensile strength is preferably 5 to 30 cN / dtex, more preferably 8 to 25 cN / dtex, even more preferably 10 to 20 cN / dtex, and even more preferably 13 to 20 cN / dtex.
[0021] When a PVA-based fiber, such as a vinylon fiber, is used as an alkali-resistant fiber, a PVA-based fiber having the following characteristics may be used. The degree of polymerization of the PVA-based polymer constituting the PVA-based fiber can be appropriately selected according to the purpose, and is not particularly limited. In consideration of the mechanical properties of the obtained fiber, the viscosity average degree of polymerization of the PVA-based polymer calculated from the viscosity of a 30°C aqueous solution is preferably about 500 to 20,000, more preferably about 800 to 15,000, and even more preferably about 1,000 to 10,000. Among these, from the viewpoint of the strength of the obtained fiber, the viscosity average degree of polymerization of the PVA-based polymer is preferably 1,000 or more, more preferably 1,200 or more, more preferably 1,500 or more, and particularly preferably 1,750 or more. The PVA-based polymer may be a medium degree of polymerization product having a viscosity average degree of polymerization of 1,000 or more and less than 3,000, or a high degree of polymerization product having an average degree of polymerization of 3,000 or more.
[0022] The saponification degree of the PVA-based polymer can also be appropriately selected according to the purpose, and is not particularly limited. From the viewpoint of the mechanical properties of the obtained fiber, the saponification degree of the PVA-based polymer may be, for example, 95 mol% or more, preferably 98 mol% or more. The saponification degree of the PVA-based polymer may be 99 mol% or more, or 99.8 mol% or more. The saponification degree of the PVA-based polymer may be, for example, 95 to 100 mol%, preferably 98 to 100 mol% (for example, 99 to 100 mol% or 99.8 mol% to less than 100 mol%). When the saponification degree of the PVA-based polymer is the above lower limit or more or within the above range, the obtained fiber may have better mechanical properties, processability, production costs, etc.
[0023] PVA-based fibers can be produced by dissolving such a PVA-based polymer in a solvent, spinning it by any of the wet, dry-wet, or dry methods, and then hot-drawing it. Wet spinning is a method in which the spinning dope is discharged directly from the spinning nozzle into a solidification bath. Dry-wet spinning is a method in which the spinning dope is discharged from the spinning nozzle into air or an inert gas at a given distance, and then introduced into a solidification bath. Dry spinning is a method in which the spinning dope is discharged into air or an inert gas. After spinning, the PVA-based fibers may be stretched as necessary. In addition, acetalization, which is generally performed on PVA-based fibers, may be performed.
[0024] The solvent used in the spinning solution for PVA-based fibers is not particularly limited as long as it is capable of dissolving PVA. For example, water, dimethyl sulfoxide (DMSO), dimethylformamide, dimethylacetamide, and polyhydric alcohols (e.g., glycerin, ethylene glycol, triethylene glycol, etc.) may be used alone or in combination. In the present invention, when wet spinning is performed, it is preferable to use water or an organic solvent as the solvent. Among these, water and DMSO are particularly preferable from the viewpoint of ease of supply and impact on the environment. The polymer concentration in the spinning solution varies depending on the composition and degree of polymerization of the PVA-based polymer and the type of solvent, but is generally 6 to 60 mass%.
[0025] The above-mentioned solvents may also be used in dry spinning, in which case either water or an organic solvent may be used.
[0026] In addition to the PVA-based polymer, the spinning dope may contain additives, etc., depending on the purpose, as long as the effects of the present invention are not impaired. Examples of additives include boric acid, surfactants, antioxidants, decomposition inhibitors, antifreezing agents, pH adjusters, masking agents, colorants, and oils. These may be contained alone or in combination of two or more.
[0027] The solvent used in the solidification bath may be appropriately selected depending on the type of solvent used in the spinning dope. When the spinning dope is an aqueous solution, the solidification bath may be, for example, an aqueous solution of an inorganic salt (e.g., sodium sulfate, ammonium sulfate, sodium carbonate, sodium hydroxide, etc.) capable of solidifying a PVA-based polymer or an alkaline aqueous solution. When the spinning dope is an organic solvent, the solidification bath may be, for example, an organic solvent capable of solidifying a PVA-based polymer, such as alcohols such as methanol, ethanol, propanol, or butanol, or ketones such as acetone, methyl ethyl ketone, or methyl isobutyl ketone.
[0028] In the present invention, PVA-based fibers obtained by dry spinning or PVA-based fibers obtained by wet spinning from a spinning dope containing water or an organic solvent as a solvent are preferred from the viewpoint of the tensile strength of the fibers.
[0029] In order to extract and remove the solvent of the spinning dope from the solidified raw yarn, the raw yarn may be passed through an extraction bath, and may be wet-stretched at the same time as extraction. After wet stretching, the fiber may be dried and, if necessary, further subjected to dry heat stretching. When stretching is performed, the total stretching ratio (product of wet stretching and stretching ratio after drying) may be, for example, 5 to 25 times, preferably about 8 to 20 times.
[0030] As the alkali-resistant fiber, commercially available fibers may be used, and examples thereof include organic fibers such as polyvinyl alcohol-based fibers manufactured by Kuraray Co., Ltd. and polypropylene fibers manufactured by Valchip Corporation, and inorganic fibers such as glass fibers manufactured by Nippon Electric Glass Co., Ltd. and Pacific Materials Corporation.
[0031] In a preferred embodiment of the present invention, the content of the alkali-resistant fiber is preferably 0.3 mass% or more, more preferably 0.5 mass% or more, even more preferably 1.0 mass% or more, and preferably 5.0 mass% or less, more preferably 4.5 mass% or less, even more preferably 4.0 mass% or less, based on the mass of the cured body. The content of the alkali-resistant fiber is preferably 0.3 to 5.0 mass%, more preferably 0.5 to 4.5 mass%, even more preferably 1.0 to 4.0 mass% based on the mass of the cured body. When the content of the alkali-resistant fiber is equal to or more than the lower limit and equal to or less than the upper limit, or within the above range, the produced cured body can have higher impact resistance, higher bending strength, and higher dimensional stability.
[0032] The content of the alkali-resistant fiber in the hardened body can be calculated from the mixing ratio of each component when preparing the hydraulic composition before hardening the hardened body. Naturally, the content of the alkali-resistant fiber in the hardened body can be obtained by this calculation whether or not the hardened body contains organic matter other than the alkali-resistant fiber.
[0033] In the pore size distribution of the cured body determined by mercury intrusion porosimetry, the ratio (B) of the pore volume (B) in the range of 11 to 300,000 nm to the pore volume (A) in the range of 6 to 10 nm is 14 or less, preferably 13 or less, more preferably 12 or less, and even more preferably 11 or less (e.g., 10 or less). The ratio (B) / (A) is usually 3 or more, preferably 4 or more, more preferably 5 or more, and even more preferably 6 or more. The ratio (B) / (A) is usually 3 to 14, preferably 4 to 13, more preferably 5 to 12, and even more preferably 6 to 11 (e.g., 6 to 10).
[0034] In a preferred embodiment of the present invention, the pore volume (A) in the range of 6 to 10 nm (generally called gel voids) in the pore size distribution of the cured body determined by mercury intrusion porosimetry is preferably 0.05 mL / g or more, more preferably 0.08 mL / g or more, even more preferably 0.10 mL / g or more, even more preferably 0.11 mL / g or more, and most preferably 0.12 mL / g or more, and may be 0.90 mL / g or less, 0.70 mL / g or less, 0.50 mL / g or less, or 0.30 mL / g or less. The pore volume (A) is preferably 0.05 to 0.90 mL / g, more preferably 0.08 to 0.70 mL / g, even more preferably 0.10 to 0.50 mL / g, even more preferably 0.11 to 0.30 mL / g, and most preferably 0.12 to 0.30 mL / g. The pore volume (A) indicates a dense structure into which water cannot penetrate, which is obtained by the reaction of the hardened matrix. When the pore volume (A) is equal to or more than the lower limit and equal to or less than the upper limit, or within the range, the hardened body can have a suitable denseness, and therefore the hardened body can have higher impact resistance, higher dimensional stability, lower water absorption, and / or higher bending strength. The pore volume (A) can be adjusted to a value equal to or more than the lower limit and equal to or less than the upper limit, or within the range, for example, by adjusting the ratio of cement, slag, slaked lime, etc., and / or by adjusting the conditions (e.g., curing conditions) when forming the hardened body.
[0035] In a preferred embodiment of the present invention, the pore volume (B) in the range of 11 to 300,000 nm (generally called capillary void) in the pore size distribution of the cured body determined by mercury intrusion porosimetry is preferably 3.0 mL / g or less, more preferably 2.0 mL / g or less, more preferably 1.9 mL / g or less, even more preferably 1.5 mL / g or less, and particularly preferably 1.3 mL / g or less. The pore volume (B) indicates a coarse structure obtained by the reaction of the cured body matrix into which water can enter, and when the pore volume (B) is equal to or less than the upper limit, the cured body can have suitable denseness, and therefore the cured body can have higher impact resistance, higher dimensional stability, lower water absorption, and / or higher bending strength. The lower limit of the pore volume (B) is not particularly limited. The pore volume (B) may be 0.3 mL / g or more, 0.5 mL / g or more, 0.7 mL / g or more, or 1.0 mL / g or more. The pore volume (B) is preferably 0.3 to 3.0 mL / g, more preferably 0.5 to 2.0 mL / g, even more preferably 0.7 to 1.9 mL / g, still more preferably 1.0 to 1.5 mL / g, and particularly preferably 1.0 to 1.3 mL / g. The pore volume (B) can be adjusted to a value not less than the lower limit and not more than the upper limit, or within the range, by, for example, adjusting the ratio of cement, slag, slaked lime, etc., and / or adjusting the conditions (e.g., pressing conditions) for molding the hardened body, and / or adjusting the particle size of the material used.
[0036] Furthermore, the ratio (B) / (A) is defined as a parameter expressing a dense structure (the gel voids). The ratio (B) / (A) means the ratio of a coarse structure to a dense structure, and the smaller the value, the denser the structure. When the ratio (B) / (A) is equal to or less than the upper limit and equal to or more than the lower limit, the hardened body can have a suitable denseness, and therefore the hardened body can have higher impact resistance, higher dimensional stability, lower water absorption, and / or higher bending strength. The ratio (B) / (A) can be adjusted to a value equal to or more than the lower limit and equal to or less than the upper limit by, for example, adjusting the ratio of cement, slag, slaked lime, etc., and / or adjusting the conditions (e.g., pressing conditions) for molding the hardened body, and / or adjusting the particle size of the material used. The pore volume (A), the pore volume (B) and the pore volume ratio (B) / (A) are determined by the method described in the Examples.
[0037] In a preferred embodiment of the present invention, the total content of calcium oxide, calcium hydroxide and calcium carbonate crystals measured by powder X-ray diffraction is preferably 15% by mass or less, more preferably 12% by mass or less, even more preferably 10% by mass or less, and particularly preferably 8% by mass or less, based on the mass of the hardened body excluding the fiber component. Calcium oxide and calcium hydroxide can be contained in the hardened body mainly as unreacted reactants (e.g., a mixture containing cement, slag and slaked lime), and calcium carbonate can be contained in the hardened body mainly as a reaction product of calcium hydroxide and carbon dioxide. Therefore, the total content being equal to or less than the upper limit means that there are few unreactants in the hardened body, that is, the reactants have reacted without excess or deficiency. When the total content is equal to or less than the upper limit, the hardened body can have a dense structure and a desired or preferred pore volume ratio (B) / (A), and the deterioration of the physical properties (e.g., impact resistance, dimensional stability and / or low water absorption) of the hardened body mainly caused by the unreactants (e.g., deterioration of physical properties over time) can be suppressed. The total content can be adjusted to the upper limit or less, for example, by adjusting the ratio of cement, slag, slaked lime, etc., by adjusting the slaked lime to have a specific average particle size in the hydraulic composition, and / or by adjusting the conditions during curing (temperature, humidity, etc.). The total content, as well as the calcium oxide crystal content, calcium hydroxide crystal content, and calcium carbonate crystal content measured by powder X-ray diffraction described later, can be measured by the method described in the examples described later. Since the lower the total content, the better, the lower limit is not particularly limited and is equal to the detection limit of the measuring device.
[0038] In a preferred embodiment of the present invention, the total content of unreacted calcium oxide and calcium hydroxide crystals among the calcium components, as measured by powder X-ray diffraction, is preferably 12 mass% or less, more preferably 8 mass% or less, and even more preferably 4 mass% or less, relative to the mass of the hardened body excluding the fiber component. Similarly, the lower limits of these contents are not particularly limited and are equal to the detection limit of the measuring device.
[0039] In one embodiment of the present invention, the hardened body further contains pulp in an amount of preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more, based on the mass of the hardened body. Pulp has the effect of improving the yield rate in the papermaking process when the hardened body is produced by a papermaking method, and the effect of increasing the impact resistance and bending strength of the hardened body. Therefore, when the pulp content is equal to or more than the lower limit, it is possible to increase the yield rate in the papermaking process when the hardened body is produced by a papermaking method, and to obtain a hardened body with higher impact resistance and higher bending strength. On the other hand, if the pulp content is too much, the water absorption of the hardened body may deteriorate. Therefore, from the viewpoint of water absorption, the pulp content is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 6.5% by mass or less, based on the mass of the hardened body. When the pulp content is equal to or less than the upper limit, it is possible to avoid problems such as a decrease in the effect of suppressing the penetration of corrosive substances (chlorine, carbon dioxide, various organic acids such as sulfate ions). The content of pulp is preferably 0.1 to 10 mass%, more preferably 1 to 8 mass%, and further preferably 2 to 6.5 mass%, based on the mass of the hardened body. The content of pulp can be calculated from the mixing ratio of each component when preparing the hydraulic composition before hardening the hardened body.
[0040] Examples of pulp include natural pulp such as wood pulp, cotton linter pulp, and hemp.
[0041] The pulp that can be blended in the hydraulic composition may be beaten or not. From the viewpoint of impact resistance and bending strength, it is preferable to use beaten pulp, and it is more preferable to use pulp whose beating degree measured in accordance with the Canadian standard type of the freeness test method JIS P8121-1976 is preferably 50 to 400 mL, more preferably 100 to 150 mL in CSF value.
[0042] Examples of pulp include conifers, broad-leaved trees, Manila hemp, Mitsumata, paper mulberry, gampi, sarago, mulberry, straw, bamboo, reed, sabai, larang grass, esparto, bagasse, sisal, kenaf, linter, banana, and waste paper. Examples of the conifers include conifers of the Cedar family, Pinaceae, Cupressaceae, and Araucaria family, and examples of the broad-leaved trees include broad-leaved trees of the Elm family, Fagaceae, Myrtaceae, Ceruleaceae, Oleaceae, Rutaceae, Betulaceae, Maple family, Juglandaceae, Tilia family, Araliaceae, Sapotaceae, Celastraceae, Apocynaceae, Verbenaceae, Magnoliaceae, and Sterculiaceae. These pulps may be bleached or unbleached pulps. The pulps may be used alone or in combination of two or more.
[0043] [Method of manufacturing the hardened body] The hardened body of the present invention is based on a hydraulic composition. That is, the hardened body of the present invention can be produced by hardening the hydraulic composition, for example, by a method (papermaking method) including filtering a slurry (hydraulic composition) prepared by suspending solids such as cement, slag, slaked lime, and alkali-resistant fiber in an aqueous medium, and molding and curing the filtered sheet-like product, or by a method including molding a hydraulic composition prepared by suspending solids such as cement, slag, slaked lime, and alkali-resistant fiber in an aqueous medium using a mold.
[0044] <Paper making method> The papermaking method includes a cylinder-net papermaking method (Hatchek method) or a Fourdrinier papermaking method, in which the filtered thin sheet-like material is successively laminated on a making roll until it reaches the desired thickness to obtain a hardened body, and a flow-on papermaking method, in which a thick slurry is supplied onto a felt and successively laminated on a making roll in one or several passes until it reaches the desired thickness to obtain a hardened body, etc. From the viewpoints of uniformity of the hardened body and ease of thickness adjustment, the cylinder-net papermaking method or the Fourdrinier papermaking method is preferred, and from the viewpoint of mass production, the cylinder-net papermaking method is more preferred.
[0045] The manufacturing method of the hardened body by the cylinder molding method is usually as follows: A step of preparing a hydraulic composition by mixing cement, slag, slaked lime, alkali-resistant fiber, water, and, if necessary, optional components described later (hydraulic composition preparation step); a step of forming the obtained hydraulic composition into a sheet using a cylinder and laminating the sheet to a desired thickness (lamination step of the sheet); A process of applying pressure to the laminated paper sheets to squeeze out the liquid and form them (squeezing and forming process); and The process of curing the sheet after squeezing (curing process) Includes.
[0046] The method for preparing the hydraulic composition is not particularly limited. The hydraulic composition can be prepared by mixing the components using a known or commonly used mixing means such as a mixer. Examples of the mixing means include mixers with high mixing performance, such as vertical mixers, blade mixers, screw mixers, cone mixers, and agitator mixers used in papermaking methods.
[0047] The mixing order of each component is not particularly limited. From the viewpoint of uniform dispersion of solid components in the hydraulic composition, when pulp is added, it is preferable to first put the pulp into water and stir, then add cement, slag, hydrated lime, and optional components other than pulp when added in any order and stir, and finally add the alkali-resistant fiber.
[0048] Examples of cement include Portland cement such as ordinary Portland cement, high-early-strength Portland cement, extra-high-early-strength Portland cement, and moderate-heat Portland cement; alumina cement; blast-furnace cement; silica cement; fly ash cement; and white Portland cement. These cements may be used alone or in combination of two or more. From the viewpoint of versatility and / or cost, it is preferable to use normal Portland cement. From the viewpoint of early strength development, it is preferable to use high-early-strength Portland cement or ultra-high-early-strength Portland cement. From the viewpoint of improving long-term strength, it is preferable to use blast-furnace cement.
[0049] The above-mentioned cements are commercially available, and an example of a commercially available product is ordinary Portland cement manufactured by Taiheiyo Cement Corporation.
[0050] In this specification, slag means steel slag. Steel slag is roughly divided into blast furnace slag and steelmaking slag, and either of them can be used in the present invention. Blast furnace slag is preferred from the viewpoint of higher impact resistance, higher dimensional stability, and lower water absorption of the hardened body. Blast furnace slag includes slowly cooled slag, which is crystalline, and granulated slag, which is amorphous, and either of them can be used in the present invention. It is preferred to use granulated slag from the viewpoint of further improving the strength of the hardened body or accelerating curing.
[0051] The Blaine specific surface area of the blast furnace slag is preferably 1000 to 9000 cm 2 / g, more preferably 2000 to 8000 cm 2 / g, and more preferably 3000 to 7000 cm 2 / g. When the Blaine specific surface area of blast furnace slag is within the above range, the blast furnace slag can have sufficient reaction sites and a suitable average particle size, and as a result, the produced hardened body can exhibit higher impact resistance, higher dimensional stability, and lower water absorption. The Blaine specific surface area of blast furnace slag can be adjusted to within the above range, for example, by crushing and classifying the blast furnace slag and using a specific fraction. The Blaine specific surface area of blast furnace slag can be measured, for example, by a laser diffraction / scattering method.
[0052] As the slaked lime, for example, solid slaked lime, slaked lime dissolved in water, or a combination thereof can be used, but is not limited thereto. In one embodiment of the present invention, it is preferable to use solid slaked lime as the slaked lime, which can react with the slag locally near the surface of the slag to obtain a hardened body having a suitable density.
[0053] In a preferred embodiment, the average particle size of the slaked lime in the hydraulic composition is preferably 3 to 600 μm, more preferably 5 to 400 μm, even more preferably 7 to 200 μm, and particularly preferably 10 to 100 μm. When the average particle size is within the above range, a hardened body having a more suitable density can be obtained. The average particle size can be adjusted to within the above range by crushing and classification. The average particle size can be determined by a general method, for example, by measuring the circle equivalent diameter of 100 randomly selected slaked lime particles using an optical microscope and calculating the average value.
[0054] In another embodiment of the present invention, it is preferable to use slaked lime dissolved in water as the slaked lime. Examples of slaked lime dissolved in water include an aqueous solution of slaked lime, such as circulating water (white water) in a papermaking process when a hardened body is produced by a papermaking method. The papermaking process circulating water may contain solid slaked lime, and such papermaking process circulating water may be used as slaked lime. Also, a combination of an aqueous solution of slaked lime other than the papermaking process circulating water and solid slaked lime may be used as slaked lime. In these cases, the slaked lime corresponds to a combination of solid slaked lime and slaked lime dissolved in water, and in one embodiment of the present invention, it is preferable to use such a combination as slaked lime. By using slaked lime dissolved in water, or a combination of solid slaked lime and slaked lime dissolved in water, the slaked lime is present in a sparsely distributed form in the hydraulic composition, and can react locally with the slag near the surface of the slag, thereby making it possible to obtain a hardened body having suitable density.
[0055] The concentration of slaked lime in the aqueous solution of slaked lime or in the circulating water in the papermaking process is preferably 3 to 12 mass %, more preferably 4 to 11 mass %, and particularly preferably 5 to 10 mass %, from the viewpoint of suitable reactivity.
[0056] As the alkali-resistant fiber, the alkali-resistant fiber described in the previous paragraph [Hardened product] can be used. The preferred embodiment of the alkali-resistant fiber described in the previous paragraph [Hardened product] is also applicable.
[0057] Examples of optional components include, in addition to the pulp mentioned above, mica, aggregates (for example, fine aggregates such as silica sand, river sand, sea sand, mountain sand, crushed sand, and coarse aggregates such as gravel and crushed stone), non-reactive fillers such as attapulgite, bentonite, wollastonite, sepiolite, light calcium carbonate, and heavy calcium carbonate; fly ash, silica fume, red mud; anionic polymer flocculants; and combinations of two or more of these. When the hydraulic composition contains these optional components, the set body of the hydraulic composition also contains the corresponding optional components. When the hydraulic composition contains silica fume, the resulting hardened body can be densified due to the pozzolanic reactivity and fine average particle size of the silica fume. The average particle size of the silica fume is usually 0.01 to 1.0 μm, preferably 0.05 to 0.5 μm, and more preferably 0.1 to 0.2 μm.
[0058] The solid content of the hydraulic composition is usually 55 to 6 mass %, preferably 40 to 8 mass %, and more preferably 25 to 10 mass %.
[0059] Based on the total solid content of the hydraulic composition, i.e., based on the total mass of the components other than water in the hydraulic composition, the amount of cement is preferably 8 to 72 mass% (more preferably 16 to 60 mass%, still more preferably 24 to 50 mass%), the amount of slag is preferably 72 to 18 mass% (more preferably 66 to 24 mass%, still more preferably 60 to 36 mass%), the amount of slaked lime is preferably 0.5 to 12 mass% (more preferably 2 to 11 mass%, still more preferably 3 to 10), the amount of alkali-resistant fiber is preferably 0.1 to 5 mass% (more preferably 0.3 to 4.5 mass%, More preferably, the ratio of the pulp is 0 to 10 mass% (more preferably, 0.1 to 10 mass%, more preferably, 1 to 8 mass%, and even more preferably, 2 to 6.5 mass%), the amount of the fly ash is preferably 0 to 10 mass% (more preferably, 1 to 8 mass%, and even more preferably, 2 to 6 mass%), the amount of the aggregate is preferably 0 to 50 mass% (more preferably, 0 to 40 mass%, and even more preferably, 0 to 35 mass%), and the amount of the silica fume is preferably 0 to 15 mass% (more preferably, 0 to 11 mass%, and even more preferably, 0 to 8 mass%). When the hydraulic composition contains an optional component other than the pulp, the fly ash, the aggregate, and the silica fume, the amount of the optional component may be appropriately selected according to the type of the optional component.
[0060] In a preferred embodiment, the amount of the strong alkaline compound relative to the total solid content of the hydraulic composition is preferably 1.0 mass% or less, more preferably 0.5 mass% or less, even more preferably 0.1 mass% or less, and particularly preferably 0 mass%. When the amount of the strong alkaline compound is less than the upper limit or 0 mass%, a geopolymer-like hardening reaction between the strong alkaline compound and slag, which can result in a porous hardened body, is unlikely to occur, so a denser hardened body can be obtained, and such a hardened body can have high impact resistance, high dimensional stability, low water absorption, and high bending strength. Strong alkaline compounds include alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide, alkali metal carbonates such as sodium carbonate and potassium carbonate, and combinations of two or more of these, but do not include alkaline earth metal hydroxides such as calcium hydroxide, or alkaline earth metal carbonates.
[0061] Next, the hydraulic composition is put into the feed tank of a wet papermaking machine, and the solid content concentration of the hydraulic composition is usually adjusted to about 10 to 1 mass % (preferably 8 to 3 mass %) by using papermaking process circulating water. The hydraulic composition supplied from the feed tank to the vat is papered up onto the surface of a cylinder with internal negative pressure in the vat by rotation, and becomes a paper sheet, which is then transported to a making roll. The making roll stacks the paper sheets to a desired thickness, and the stacked paper sheets are cut to a predetermined length.
[0062] In a preferred embodiment, the yield rate in the papermaking process is preferably 85% or more, more preferably 90% or more. When the yield rate is equal to or more than the lower limit, higher bending strength, higher interlayer adhesion strength, and / or lower dimensional change rate can be obtained. The yield rate can be adjusted to equal to or more than the lower limit by adjusting the Blaine specific surface area of the slag, selecting the mesh size of the circular mesh, and / or adjusting the degree of beating of the beaten pulp when added. From the viewpoint of achieving both the yield rate and productivity, the mesh size of the circular mesh is preferably 45 to 55 meshes per inch. The yield rate in the papermaking process can be determined, for example, by the following method. The slurry poured into the cylindrical net is scooped up and its mass (A1) is measured. The solids are filtered out using a general filtering device (e.g., a Nutsche and suction bottle), dried in a 105°C dryer for 12 hours or more until the dry mass becomes constant, and the mass of the solids (B1) is measured. The concentration C1 of the slurry poured into the cylindrical net is calculated using the following formula. Concentration C1=(B1 / A1)×100 Similarly, the slurry that has passed through the cylindrical net is scooped up and its concentration C2 is calculated using the following formula. Concentration C2=(B2 / A2)×100 Here, A2 is the mass of the slurry that has passed through the mesh screen and B2 is the mass of the solid content. The retention rate in the papermaking process can be calculated using the following formula. Yield rate in papermaking process (%) = {(C1-C2) / C1} x 100
[0063] The number of sheets to be laminated depends on the solids concentration of the hydraulic composition and the thickness of the hardened body to be produced, but is usually 12 to 18 sheets when the hardened body has a thickness of about 6 mm.
[0064] The cut sheets are then squeezed and shaped by applying pressure to them in a press. The pressure applied by the press is preferably 2 to 30 MPa, more preferably 3 to 27 MPa, and particularly preferably 4 to 25 MPa. The time for applying the pressure is usually 10 to 60 minutes, preferably 15 to 50 minutes, and more preferably 20 to 40 minutes. By setting the pressure within the above range or setting the time for applying the pressure within the above range, the desired pore volume ratio (B) / (A) can be obtained in the cured product, and as a result, a cured product having higher impact resistance, higher dimensional stability, lower water absorption, and / or higher bending strength can be obtained.
[0065] The sheet from which the liquid has been squeezed is then cured. Curing progresses the hardening. Hardening is due to the hydration reaction (setting reaction) of cement and slag, but if the moisture in the sheet evaporates, the hydration reaction is inhibited and hardening may not progress. Therefore, it is preferable to perform the first curing in a high humidity atmosphere where the moisture in the sheet does not evaporate, that is, in an atmosphere with a relative humidity of preferably 30 to 100%, more preferably 50 to 100%, even more preferably 65 to 100%, even more preferably 80 to 100%, and particularly preferably 90 to 100% (for example, 100%), and perform the second curing in a high humidity atmosphere (preferably an atmosphere of 30 to 100%, more preferably 40 to 90%, and even more preferably 50 to 80%) by putting the sheet in a container or bag that does not allow moisture to pass through, or by sandwiching the sheet between plastic plates, plastic films (polyethylene sheets, etc.), or metal plates, so that the moisture in the sheet is less likely to evaporate.
[0066] The curing temperature is not particularly limited. The primary curing temperature is, for example, 10 to 90°C, preferably 30 to 80°C, and more preferably 40 to 80°C. The curing temperature may be changed midway within the above range. The secondary curing temperature is, for example, 10 to 70°C, and preferably 20 to 50°C. The primary curing time depends on the composition of the hydraulic composition and the curing temperature, but is usually 6 to 48 hours, preferably 8 to 36 hours, and more preferably 12 to 24 hours. The secondary curing time is usually 1 to 14 days.
[0067] In addition, underwater curing may be performed as a secondary curing. In this case, the water temperature is usually 10 to 30°C, and the curing time is 8 hours to 13 days. After underwater curing at a water temperature of 10 to 30°C for 4 to 24 hours, the secondary curing described in the previous paragraph may be performed for 2 to 13 days.
[0068] After the secondary curing, the composition is dried to obtain a hardened body. The drying method is not particularly limited as long as a uniformly dried hardened body can be obtained. Usually, the equilibrium moisture content of the hardened body (for example, the moisture content reached when the hardened body is stored in a well-ventilated room for 7 days or more) is about 6% by mass to about 10% by mass, so the hardened body is dried to a moisture content similar to the equilibrium moisture content. The moisture content and equilibrium moisture content of the hardened body can be simply measured using a Kett moisture meter. Alternatively, the hardened body after drying can be weighed (W 12 ), and then the hardened body was dried in an air dryer equipped with an agitator at 105°C until it reached a constant weight and weighed (W 13 ) and the following formula: {(W 12 -W 13 ) / W 13}×100 It can also be calculated by:
[0069] <Method including molding using a mold> The method including molding using a mold usually includes the steps of: A step of preparing a hydraulic composition by mixing cement, slag, slaked lime, alkali-resistant fiber, water, and, if necessary, the optional components described above, and the following steps (i) to (iv): (i) pouring the obtained hydraulic composition into an open formwork (casting method); (ii) a step of dehydrating the hydraulic composition by pressing or suction (dehydration molding method); (iii) injecting the hydraulic composition into a closed form (injection molding method); and (iv) A process of passing the hydraulic composition through a die to form a product of a specific shape (extrusion molding method). The method includes any one of the steps. In the extrusion molding method, a vacuum extruder may be used. In addition, during molding, pressure and / or vibration may be applied as necessary, and the hydraulic composition may be pressed by a press using an upper mold or a roll or the like.
[0070] The step of preparing the hydraulic composition in the method including molding using a mold may be carried out in the same manner as the step of preparing the hydraulic composition in the papermaking method. A predetermined amount of the obtained hydraulic composition may be set in a press lower mold, and dehydrated and molded by pressing while applying pressure. The pressure to be applied may be, for example, 1 to 30 MPa, and the pressing time may be 0.01 to 30 minutes.
[0071] The curing after the molding may be carried out in the same manner as the curing step in the papermaking method. A hardened body is obtained by drying after the secondary curing. This drying method may also be carried out in the same manner as the drying method in the papermaking method.
[0072] The impact strength of the cured product when dry is preferably 3.0 kJ / m 2 More preferably, 3.5 kJ / m 2 More preferably, 4.0 kJ / m 2 The upper limit of the impact strength of the cured body when dry is not limited, but is usually 20.0 kJ / m 2 The impact strength of the cured product in a dry state is preferably 3.0 to 20.0 kJ / m 2 , more preferably 3.5 to 20.0 kJ / m 2 , and more preferably 4.0 to 20.0 kJ / m 2 It is. The impact strength of the cured product when it absorbs water is preferably 5.0 kJ / m 2 More preferably, 5.3 kJ / m 2 More preferably, 5.5 kJ / m 2 The upper limit of the impact strength of the hardened body when it absorbs water is not limited, but is usually 20 kJ / m 2 The impact strength of the cured body when it absorbs water is preferably 5.0 to 20.0 kJ / m 2 , more preferably 5.3 to 20.0 kJ / m 2 , and more preferably 5.5 to 20.0 kJ / m 2 It is.
[0073] The dimensional change rate of the cured body is preferably 0.20% or less, more preferably 0.16% or less, and even more preferably 0.12% or less. The lower limit of the dimensional change rate of the cured body is not limited, but is usually 0.01% or more. The dimensional change rate is preferably 0.01 to 0.20%, more preferably 0.01 to 0.16%, and even more preferably 0.01 to 0.12%.
[0074] When the cured body does not contain pulp, the water absorption of the cured body determined in accordance with JIS A 5430:2018 is preferably 1 to 25%, more preferably 3 to 20%, and even more preferably 5 to 15%. When the cured body contains pulp, the water absorption of the cured body determined in accordance with JIS A 5430:2018 is preferably 5 to 40%, more preferably 7 to 30%, and even more preferably 10 to 20%.
[0075] The bending strength of the cured body when dry is preferably 7N / mm 2 More preferably, 10N / mm 2 More preferably, 15N / mm 2 The upper limit of the bending strength of the cured body when dry is not limited, but is usually 100 N / mm 2 The bending strength of the cured body in a dry state is preferably 7 to 100 N / mm 2 , more preferably 10 to 100N / mm 2 , and more preferably 15 to 100 N / mm 2 It is. The bending strength of the hardened body when it absorbs water is preferably 6N / mm 2 More preferably, 10N / mm 2 More preferably, 14N / mm 2 The upper limit of the bending strength of the hardened body when it absorbs water is not limited, but is usually 100 N / mm 2 The bending strength of the cured body when it absorbs water is preferably 6 to 100 N / mm 2 , more preferably 10 to 100N / mm 2 , more preferably 14 to 100 N / mm 2 It is.
[0076] The physical properties of the cured product described above (impact strength when dry, impact strength when absorbing water, dimensional change rate, water absorption rate, flexural strength when dry, and flexural strength when absorbing water) can be measured by the method described in the Examples.
[0077] The cured product of the present invention has high impact resistance, high dimensional stability, low water absorption and high bending strength, and can therefore be suitably used as building boards for interior and exterior wall materials, roofing materials, flooring materials, etc. Accordingly, the present invention also includes building boards comprising the cured product of the present invention and building boards made of the cured product of the present invention. EXAMPLES
[0078] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The physical properties in the examples and comparative examples were measured or evaluated according to the following procedures.
[0079] <Content of calcium silicate, calcium aluminate, calcium oxide, calcium hydroxide and calcium carbonate crystals> The hardened body was crushed in a mortar, and the fibers were removed from the crushed material with tweezers. The crushed material from which the fibers had been removed was analyzed by powder X-ray diffraction to determine the content of calcium silicate, calcium aluminate, calcium oxide, calcium hydroxide, and calcium carbonate crystals contained in the hardened body. The measurement conditions for powder X-ray diffraction were tube voltage: 40 kV, tube current: 15 mA, scanning range: 2θ = 5 to 70°, step width: 0.01°, and scan speed: 2° / min. PDXL2 (Rigaku Corporation) was used for the Rietveld analysis. In the quantitative analysis, alite, belite, ubicC3A, orthorhombic-C3A, C4AF, corundum (internal standard), calcite, portlandite, and lime were appropriately set according to the phases contained in the sample, and the crystal content of each mineral phase was quantified collectively. Note that, for the quantitative condition of C3A, two types of polymorphism were set for calculation, but the evaluation was performed by summing both polymorphisms and determining the amount of C3A.
[0080] <Pore volume and pore volume ratio> Two test pieces of about 1 cm square were cut out from the hardened body to be measured, and dried at 105°C ± 5°C for 12 hours or more, then placed in a desiccator with humidity control using silica gel and left to stand until the temperature reached 20°C ± 1.5°C. The pore size distribution of these test pieces was measured by mercury intrusion porosimetry using a mercury intrusion porosimetry pore volume measuring device (Micromeritics' "MicroActive AutoPore V 9600"). From the log differential pore volume obtained from the obtained pore size distribution, the pore volume (A) in the range of 6 to 10 nm and the pore volume (B) in the range of 11 to 300,000 nm of each test piece were calculated. The ratio of the pore volume (B) in the range of 11 to 300,000 nm to the pore volume (A) in the range of 6 to 10 nm for each test piece was calculated using the following formula, and the average value was adopted as the pore volume ratio (B) / (A) of the hardened body. Pore volume ratio (B) / (A)={pore volume in the range of 11-300,000 nm (B)} / {pore volume in the range of 6-10 nm (A)}
[0081] <Average fiber diameter, aspect ratio, and tensile strength of alkali-resistant fibers> The average fiber diameter of the alkali-resistant fibers was determined by randomly selecting 100 fibers, measuring the fiber diameter at the center in the longitudinal direction of each fiber using an optical microscope, and calculating the average value. The aspect ratio (fiber length / fiber diameter) of the alkali-resistant fiber was calculated from the average fiber length and the average fiber diameter. The average fiber length of the alkali-resistant fiber was determined in accordance with JIS L 1015:2010. The tensile strength of the alkali-resistant fiber was determined in accordance with JIS L 1015:2010.
[0082] <Impact strength> Six Type 1 test pieces conforming to JIS K 7111-1:2012 were cut out from the hardened specimen to be measured. To measure the impact strength in the dry state, three test pieces were first dried for 72 hours in an air dryer equipped with an agitator set at 40°C. The test pieces were then taken out and placed in a desiccator whose humidity had been conditioned with silica gel, and left to stand until the temperature reached 20°C ± 1.5°C. The impact strength (without notch) of each test piece was measured in accordance with JIS K 7111-1:2012, and the average value was used as the impact strength of the cured body in the dry state. To measure the impact strength when water is absorbed, first, three test pieces were immersed in water at 20°C for 72 hours. Next, the test pieces were taken out, and the water adhering to the surface was wiped off. Immediately after that, the impact strength (without notch) of each test piece was measured in accordance with JIS K 7111-1:2012, and the average value was used as the impact strength of the cured body when water is absorbed. The impact strength in the dry state and when water is absorbed was measured using a Charpy (digital) impact tester, model DG-CB, manufactured by Toyo Seiki Seisakusho Co., Ltd.
[0083] <Dimensional change rate> The dimensional change rate (length change rate) of the cured body was measured in accordance with JIS A 5430:2018. Specifically, three rectangular test pieces with a length of about 160 mm and a width of about 50 mm were cut out from the cured body to be measured, and then these test pieces were placed in a dryer, and the temperature inside the dryer was kept at 60°C ± 3°C for 24 hours. After that, the test pieces were taken out and placed in a desiccator whose humidity was adjusted with silica gel, and left until the temperature reached 20°C ± 1.5°C. Next, milky glass was attached to each test piece, and a marking was engraved so that the distance between the marks was about 140 mm. The length between the marks was measured with a comparator with an accuracy of 1 / 500 mm, and the length was defined as L1 (mm). Next, the test pieces were set upright so that the longitudinal direction was horizontal, and the upper end of the test piece was about 30 mm below the water surface, and immersed in water at 20°C ± 1.5°C. After 24 hours, the test pieces were taken out of the water, the water adhering to the surface was wiped off, and the length between the marks was measured again, and this length was designated as L2 (mm). The dimensional change rate (%) due to water absorption was calculated for each test piece using the following formula, and the average value was used as the dimensional change rate of the hardened body. Dimensional change rate = {(L2-L1) / L1} x 100
[0084] <Water absorption rate> The water absorption rate of the cured body was measured in accordance with JIS A 5430:2018. Specifically, four rectangular test pieces measuring approximately 180 mm in length and 50 mm in width were cut out from the cured body to be measured, and the test pieces were then immersed in water at 20°C ± 1.5°C. After 24 hours had passed, the test pieces were removed, the water adhering to the surface was wiped off, and the mass of each test piece (the mass of the test piece when it absorbed water W 14 ) was measured. Next, these test pieces were placed in a dryer equipped with an agitator adjusted to 105°C ± 5°C, and after drying for 24 hours, they were removed and placed in a desiccator whose humidity had been adjusted with silica gel, and left to stand until the temperature reached room temperature of 20°C ± 1.5°C. After that, the mass of each test piece (mass of test piece when dry, W0) was measured. The water absorption rate (%) of each test piece was calculated using the following formula, and the average value was used as the water absorption rate of the cured body. Water absorption rate={(W 14 -W0) / W0}×100
[0085] <Bending strength> Eight rectangular test pieces, each approximately 180 mm long and 50 mm wide, were cut out from the hardened specimen to be measured. To measure the flexural strength in the dry state, four test pieces were first dried for 72 hours in an air dryer equipped with an agitator set at 40°C. The test pieces were then taken out and placed in a desiccator whose humidity had been conditioned with silica gel, and left to stand until the temperature reached 20±1.5°C. The flexural strength of each test piece was measured in accordance with JIS A 1408:2017, and the average value was used as the flexural strength of the cured body in the dry state. To measure the bending strength when water is absorbed, four test pieces were first immersed in water at 20°C for 72 hours. The test pieces were then taken out and the water on the surface was wiped off. The bending strength of each test piece was then immediately measured in accordance with JIS A 1408:2017, and the average value was used as the bending strength of the hardened body when water is absorbed. The bending strength in the dry and wet conditions was measured using an autograph "AG50kNX" manufactured by Shimadzu Corporation, with a central loading method, a bending span of 14.6 cm, and a test speed (loading head speed) of 20 mm / min.
[0086] [Example 1] Pulp (NBKP, Cellofiber manufactured by Partex Co., Ltd., CSF value: 115 mL) was dispersed in water. The resulting dispersion was mixed with ground granulated blast furnace slag powder (DC Corporation: Blaine specific surface area: 4000 cm 2 100g), ordinary Portland cement (ordinary Portland cement manufactured by Taiheiyo Cement Corporation), fly ash (equivalent to Type II manufactured by Shiden Business Co., Ltd.) and slaked lime (industrial slaked lime No. 1 manufactured by Kochi Lime Industry Co., Ltd., average particle size: 20 μm) were charged and mixed. Polyvinyl alcohol fiber 1 (average fiber diameter: 14 μm, aspect ratio: 429, tensile strength: 14.3 cN / dtex, shown as PVA1 in Table 1) was added as an alkali-resistant fiber to the obtained mixture and further mixed. The mass ratio of each component is as shown in Table 1, and a hydraulic composition with a solid content concentration of 16 mass% was obtained. The obtained hydraulic composition was transferred to a feed tank of a constant-volume feeder, and was fed from the feed tank to a cylinder. The solid content of the hydraulic composition was adjusted to 4% by mass using circulating water in the papermaking process, and papermaking was performed using a mini-Hatchek machine. Next, 15 sheets of the papermaking sheets obtained in the cylinder process were stacked on a making roll, and the stacked papermaking sheets were pressed for 20 minutes while applying a pressure of 5.0 MPa to squeeze out the liquid. The sheet after squeezing out the liquid was cured in a constant-temperature and constant-humidity curing device at a temperature of 50°C and saturated humidity (RH 98%) for 24 hours, and then wrapped in a wrap sheet and cured for 13 days in an environment at a temperature of 20°C and humidity of 60% (total curing for 14 days). The sheet from which the wrap sheet was removed was dried in a roll dryer-type dryer set at a temperature of 120°C for 2 hours to obtain a hardened material. The physical properties of the hydraulic composition and the set body were measured and evaluated by the methods described above. The results are shown in Table 1.
[0087] [Example 2 and Comparative Examples 1-2] A hydraulic composition and its hardened product were obtained in the same manner as in Example 1, except that the materials and / or amounts to be mixed were changed as shown in Table 1. The physical properties of the hydraulic composition and the hardened product were measured and evaluated. The results are shown in Table 1.
[0088] [Example 3] A hydraulic composition and its hardened product were obtained in the same manner as in Example 2, except that the pressure applied to the laminated papermaking sheets was changed from 5.0 MPa to 10.0 MPa, and the physical properties of the hydraulic composition and the hardened product were measured and evaluated. The results are shown in Table 1.
[0089] [Example 4] A hydraulic composition and its hardened body were obtained in the same manner as in Example 1, except that, as the alkali-resistant fiber, polyvinyl alcohol fiber 2 (average fiber diameter: 7 μm, aspect ratio: 571, tensile strength: 14.5 cN / dtex, shown as PVA2 in Table 1) was used instead of polyvinyl alcohol fiber 1, and the amounts of the alkali-resistant fiber and fly ash were changed as shown in Table 1. The physical properties of the hydraulic composition and the hardened body were measured and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0090] [Examples 5 to 6] A hydraulic composition and its hardened product were obtained in the same manner as in Example 1, except that polyvinyl alcohol fiber 3 (average fiber diameter: 14 μm, aspect ratio: 429, tensile strength: 12.6 cN / dtex, shown as PVA3 in Table 1) or polypropylene fiber (average fiber diameter: 17 μm, aspect ratio: 353, tensile strength: 5.3 cN / dtex, shown as PP in Table 1) was used as the alkali-resistant fiber instead of polyvinyl alcohol fiber 1. The physical properties of the hydraulic composition and the hardened product were measured and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0091] [Table 1]
[0092] [Example 7] 3.5 parts by mass of pulp (NBKP, Cellofiber manufactured by Partex Co., Ltd., CSF value: 115 mL) was dispersed in water. 28 parts by mass of ground granulated blast furnace slag (manufactured by DC Corporation: Blaine specific surface area: 4000 cm) was added to the obtained dispersion. 2100 parts by mass of 1000g / g), 43 parts by mass of ordinary Portland cement (ordinary Portland cement manufactured by Taiheiyo Cement Corporation), 3 parts by mass of fly ash (equivalent to Type II manufactured by Shiden Business Co., Ltd.), 6 parts by mass of silica fume (EFACO manufactured by Tomoe Engineering, average particle size: 2 μm), and 14.5 parts by mass of non-reactive filler were added and mixed. 2 parts by mass of polyvinyl alcohol fiber 2 (average fiber diameter: 7 μm, aspect ratio: 571, tensile strength: 14.5 cN / dtex) was added as an alkali-resistant fiber to the obtained mixture and further mixed. A hydraulic composition with a solid content concentration of 16% by mass was obtained. A set product was obtained in the same manner as in Example 1 except for using the obtained hydraulic composition, and the physical properties of the hydraulic composition and the set product were measured and evaluated. The physical properties after 14 days of curing are as follows: Total content of calcium silicate and calcium aluminate: 8.81 mass%, calcium oxide content: 1.55 mass%, calcium hydroxide content: 0.32 mass%, calcium carbonate content: 2.67 mass%, total content of calcium oxide, calcium hydroxide and calcium carbonate: 4.54 mass%, pore volume ratio (B) / (A): 5.64, pore volume (A): 0.3407 mL / g, pore volume (B): 1.9203 mL / g, impact strength when dry: 3.55 kJ / m 2 , Impact strength when absorbing water: 4.67kJ / m 2 , Dimensional change rate: 0.15%, Water absorption rate: 20.6%, Bending strength when dry: 32.3N / mm 2 , Bending strength when absorbing water: 22.3N / mm 2 .
[0093] [Example 8] Add 31.75 parts by mass of granulated blast furnace slag powder (manufactured by DC Corporation: Blaine, specific surface area: 4000 cm) to the water. 2 / g), 28 parts by mass of ordinary Portland cement (Taiheiyo Cement Corporation: ordinary Portland cement), 3.18 parts by mass of fly ash (Yoshiden Business Corporation: equivalent to Type II), 5 parts by mass of slaked lime (Kochi Sekki Kogyo Co., Ltd.: industrial slaked lime No. 1, average particle size: 20 μm), and 31.16 parts by mass of silica sand (Tohoku Silica Sand Co., Ltd.: No. 5 silica sand, average particle size: 425 μm) were added and mixed. 0.91 parts by mass of polyvinyl alcohol fiber 4 (average fiber diameter: 26 μm, aspect ratio: 231, tensile strength: 13.8 cN / dtex) was added as an alkali-resistant fiber to the obtained mixture and further mixed. A hydraulic composition with a solid content concentration of 16% by mass was obtained. A predetermined amount of the obtained hydraulic composition was set in a press lower mold, dehydrated and molded by pressing for 0.5 minutes while applying a pressure of 5 MPa, and cured and dried under the same conditions as in Example 1 to obtain a hardened body. The physical properties of the obtained hydraulic composition and the set body were measured and evaluated in the same manner as in Example 1. The physical properties after 14 days of curing are as follows: Total content of calcium silicate and calcium aluminate: 5.01 mass%, calcium oxide content: 1.93 mass%, calcium hydroxide content: 3.2 mass%, calcium carbonate content: 0.89 mass%, total content of calcium oxide, calcium hydroxide and calcium carbonate: 6.02 mass%, pore volume ratio (B) / (A): 11.06, pore volume (A): 0.0693 mL / g, pore volume (B): 0.7661 mL / g, impact strength when dry: 3.8 kJ / m 2 , Impact strength when absorbing water: 5.1 kJ / m 2 Dimensional change rate: 0.14%, Water absorption rate: 19.6%, Bending strength when dry: 12.1N / mm 2 , Bending strength when absorbing water: 8.9N / mm 2 . [Industrial Applicability]
[0094] The cured product of the present invention has high impact resistance, high dimensional stability, low water absorption, and high bending strength, and can therefore be suitably used for building boards such as interior and exterior wall materials, roofing materials, and flooring materials, as well as civil engineering components.
Claims
[Claim 1] A hardened body of a hydraulic composition, The hardened body includes an alkali-resistant fiber, a calcium silicate, and a calcium aluminate, A hardened body, in which the ratio of the volume of pores in the range of 11 to 300,000 nm to the volume of pores in the range of 6 to 10 nm in a pore size distribution of the hardened body determined by mercury intrusion porosimetry is 14 or less.
Citation Information
Patent Citations
Curing composition using no cement
JP2012171855A
Inorganic board
JP2013216534A
Layered molded plate and method for manufacturing the same
WO2022004640A1
Cured body reinforced with fibers
WO2022004643A1
Cited By
Building materials for 3D printers, manufacturing method for building materials for 3D printers, and manufacturing method for buildings
JP7784587B1
